2012
DOI: 10.1007/s40003-012-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waste Water Irrigation on Physical and Biochemical Characteristics of Soil and Metal Partitioning in Beta vulgaris L.

Abstract: The present study deals with the assessment of changes in physical and biochemical characteristics of soil and metal partitioning in Beta vulgaris L. grown in farmer's fields irrigated with waste water in Dinapur and Lohta areas of Varanasi, India, during December to February, 2007February, -2008February, and 2008February, -2009. Nutrient concentrations, organic carbon, microbial biomass, C, N, and P, enzymatic activities and heavy metal concentrations in soil and plant parts were estimated at waste water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 38 publications
3
22
0
1
Order By: Relevance
“…In comparison to clean groundwater-irrigated soil and soil without any compost, wastewater-irrigated soil and soil containing compost or sewage sludge have some advantages such as: (i) more organic carbon, (ii) more available nitrogen, phosphorus and potassium, (iii) more crop production, (iv) better soil physical, chemical and biological properties, (v) more available water content and (vi) less erosion (Siebe, 1998;Tejada et al, 2001;Zheljazkov and Warman, 2004;Wei and Liu, 2005;Tabari and Salehi, 2009;Baldantoni et al, 2010;Jalali and Arfania, 2010;Mojiri, 2010;Singh and Agrawal, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to clean groundwater-irrigated soil and soil without any compost, wastewater-irrigated soil and soil containing compost or sewage sludge have some advantages such as: (i) more organic carbon, (ii) more available nitrogen, phosphorus and potassium, (iii) more crop production, (iv) better soil physical, chemical and biological properties, (v) more available water content and (vi) less erosion (Siebe, 1998;Tejada et al, 2001;Zheljazkov and Warman, 2004;Wei and Liu, 2005;Tabari and Salehi, 2009;Baldantoni et al, 2010;Jalali and Arfania, 2010;Mojiri, 2010;Singh and Agrawal, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The heavy metal pollution index (HMPI) was calculated by the following formula to show the level of contamination in water [39].…”
Section: Water Quality Assessmentmentioning
confidence: 99%
“…Where C i and S i are heavy metal content in a water sample and permitted standard of the same metal (μg.Lit -1 ), respectively. When the HMPI values exceed than 1.0, water is said to be contaminated by anthropogenic inputs and requires continuous environmental monitoring of the area [39].…”
Section: Hmpi = C I /S Imentioning
confidence: 99%
See 1 more Smart Citation
“…The periodic monitoring of the quality of this water is necessary to detect pollution flows and to restrict its environmental impacts. Singh and Agrawal (2012) reported that the long-term irrigation with waste water led to the soil pH decreased, whereas organic C, total N, available P, and exchangeable cations increased at irrigated sites as compared to the soil irrigated by clean water. Goher et al (2014) pointed out that the Ismailia canal is exposed to deterioration in its water quality because it passes through many towns and villages where some the discharged waste is thrown into the waterway.…”
Section: Introductionmentioning
confidence: 99%